2012
DOI: 10.1007/s12550-012-0130-2
|View full text |Cite
|
Sign up to set email alerts
|

Mould and mycotoxin contamination of pig feed in northwest Croatia

Abstract: The aim of this study was to investigate the contamination of pig feed with moulds and the occurrence of mycotoxins. A total of 30 feed samples were collected at different animal feed factories in the north-western part of Croatia. Mycological analysis showed that the total number of moulds ranged from 1 × 10(3) to 1 × 10(5) cfu/g with samples contaminated with Aspergillus spp. (63 %), Penicillium spp. (80 %), and Fusarium spp. (77 %). A determination of aflatoxin B1 (AFB1), ochratoxin A (OTA), zearalenone (ZE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 18 publications
3
17
0
Order By: Relevance
“…A higher ZEA concentration than the maximum recommended was determined in about 2% of the total number of feed samples, with a maximum concentration of 558 μg/kg determined in feed for calves in the eastern part of the country. In this study it was also observed that the samples in which the low concentrations of DON were determined have also low concentrations of ZEA, or both mycotoxins were not detected, or mostly the results indicate on both higher concentrations as in our earlier study performed on feed for fattening pigs (Pleadin et al, 2012b).…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…A higher ZEA concentration than the maximum recommended was determined in about 2% of the total number of feed samples, with a maximum concentration of 558 μg/kg determined in feed for calves in the eastern part of the country. In this study it was also observed that the samples in which the low concentrations of DON were determined have also low concentrations of ZEA, or both mycotoxins were not detected, or mostly the results indicate on both higher concentrations as in our earlier study performed on feed for fattening pigs (Pleadin et al, 2012b).…”
Section: Resultssupporting
confidence: 65%
“…In the determination of their concentrations the ELISA method was used. Data of methods validation for each analyzed mycotoxin in feed samples was earlier published (Pleadin et al, 2012b). The obtained results of mycotoxins concentration according to country regions (central, eastern and north) and types of feed (poultry, pig and calves) are shown in Table 1 and Table 2, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Kosicki et al (2016) reported that 5% of examined samples were contaminated with AF. In a study performed in Croatia, Pleadin et al (2012) found a 13.3% prevalence of AFB 1 in feed for fattening pigs with a mean concentration of 1.10 ± 0.51 μg/kg (max. 1.53 μg/kg).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to our study, Kosicki et al (2016) reported a higher prevalence of DON in cereal grain samples (98%) and a similar prevalence in maize (89%). In a Croatian study by Pleadin et al (2012), the DON prevalence in feed for fattening pigs was 96.6% with a mean concentration of 817 ± 447 μg/kg (max. 1,860 μg/kg).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation